The Influence of Service Quality and Product Quality on Consumer Satisfaction at McDonald's Nangka Denpasar Fast Food Restaurant - Handayani, Ni Made Dwi; Setiawan , I Gede Adi (The Journal of Management, Digital Business, and Entrepreneurship, 2024)
Changes in modern society's lifestyle have driven an increase in food consumption in fast food restaurants, including McDonald's which is growing rapidly in Indonesia. In the context of tight business competition, service quality and product quality are two crucial factors that influence the level of consumer satisfaction. This study aims to analyze the effect of service quality and product quality on consumer satisfaction at McDonald's Nangka Denpasar. Service quality includes aspects such as reliability, responsiveness, assurance, empathy, and physical evidence, while product quality includes freshness, cleanliness, safety, consistency, and taste of food. Consumer satisfaction is positioned as a dependent variable influenced by both independent variables. This study uses a quantitative approach with associative methods and multiple linear regression analysis to test the formulated hypotheses. The population of the study were McDonald's Nangka Denpasar consumers who had consumption experience, with data collected through the distribution of Likert-scale questionnaires. Based on the results of the study, it was found that service quality had no effect on consumer satisfaction, while product quality had an effect on consumer satisfaction at McDonald's fast food restaurants on Jalan Nangka Denpasar. The results of this study are expected to provide empirical contributions in formulating strategies for improving fast food restaurant services and products that are more oriented towards customer needs and satisfaction. These findings can also be the basis for managerial decision making in order to increase customer loyalty and competitive advantage in the fast food restaurant industry.